Contribution to the knowledge of the genus Singilis Rambur, 1837 of Africa (Coleoptera: Carabidae: Lebiini). Part IV - Anichtchenko, Alexander (Zootaxa, 2016)
Nine new species of the genus Singilis from Africa are described: Singilis (s.str.) shavrini sp. n. (Kenya, Tanzania), S. (s.str.) africaorientalis sp. n. (Ethiopia, Somalia, Tanzania, Kenya, RSA, Zambia, Zimbabwe), S. (s.str.) burtoni sp. n. (Zambia, Zimbabwe), S. (s.str.) paganeli sp. n. (RSA), S. (s.str.) somalicus sp. n. (Somalia), S. (s.str.) haekeli sp. n. (Zambia), S. (s.str.) crypticus sp. n. (Cameroon), S. (s.str.) pallens sp. n. (Namibia) and S. (s.str.) parvulus sp. n. (Zimbabwe). One new subspecies from Kenya, S. (s.str.) africaorientalis kenyacus ssp. n., is described too. Differential diagnosis of the related species Singilis (s.str.) allardi (Basilewsky, 1963), S. (s.str.) ambulans (Peringuey, 1896), S. (s.str.) cribricollis (Peringuey, 1904), S. (s.str.) pusillus (Peringuey, 1898) and S. (s.str.) zonata Chaudoir, 1878 is also proposed. Illustrations of habitus and aedeagus for every species is provided, and new country records are given.